MONITORING SUPLAI TEGANGAN PADA MOTOR INDUKSI TIGA FASA MENGGUNAKAN MIKROKONTROLER ARDUINO DAN SENSOR TEGANGAN ZMPT101B - Putri Ramadhani Adam; Purwanto Gendroyono; Nur Hanifah Yuninda (Journal of Electrical Vocational Education and Technology, 2020)
ABSTRACT The purpose of this study is to create a three-phase induction motor voltage monitoring system based on Arduino Uno microcontroller using a ZMPT101B voltage sensor. In addition, this study aims to determine the percentage of source voltage unbalance entering the 3 phase induction motor based on the National Standard for Electric Power System and Equipment ANSI Std C84.1-1995, NEMA Std MGI.2009 from the results of monitoring equipment that has been was made. The research method used by the author is a laboratory experimental method which includes manipulation, control, and observation. The results showed that the value of the percentage of voltage unbalance, the average for the morning the value is still below 1%. As for the value of the percentage of voltage unbalance in the afternoon and evening, the value is already above 1%. If according to the standard, the percentage of voltage unbalance permitted without derating (decreasing power) based on NEMA is 1%. Meanwhile, the maximum percentage of allowable voltage unbalance is 5%. So, the results of the research data of the three times the safest condition is in the morning. Meanwhile, research data taken during the afternoon and evening conditions are still safe but there will be a decrease in power. In addition, the comparison of the ZMPT101B voltage sensor with a digital AVO meter when detecting the voltage has an average error of 0.07% for the first ZMPT101B voltage sensor, 0.28% for the second ZMPT101B voltage sensor and 0.15% for the sensor the third voltage ZMPT101B. So that it can be said that the voltage monitoring system that is made in accordance with the provisions and can be applied as learning by students of Electrical Engineering Education. ABSTRAK Penelitian ini bertujuan untuk membuat sistem monitoring suplai tegangan motor induksi tiga fasa berbasis mikrokontroler Arduino Uno menggunakan sensor tegangan ZMPT101B. Selain itu, dalam penelitian ini bertujuan untuk mengetahui persentase ketidakseimbangan tegangan sumber yang masuk pada motor induksi 3 fasa berdasarkan standar The National Standard for Electric Power System and Equipment ANSI Std C84.1-1995, NEMA Std MGI.2009 dari hasil monitoring alat yang telah dibuat. Metode penelitian yang digunakan penulis yaitu metode eksperimen laboratorium yang meliputi manipulasi, pengendalian, dan pengamatan. Hasil penelitian menunjukkan bahwa nilai persentase ketidakseimbangan tegangan, rata rata untuk di waktu pagi nilainya masih di bawah 1 %. Sedangkan untuk nilai persentase ketidakseimbangan tegangan di waktu siang dan sore hari nilainya sudah di atas 1 %. Jika sesuai dengan standar, persentase ketidakseimbangan tegangan yang diijinkan tanpa melakukan derating (penurunan daya) berdasarkan NEMA adalah 1 %. Sedangkan, maksimum persentase ketidakseimbangan tegangan yang diijinkan adalah 5 %. Maka, hasil dari data penelitian ketiga waktu tersebut yang paling aman kondisinya adalah di waktu pagi hari. Sedangkan, data penelitian yang diambil saat siang dan sore hari kondisinya masih aman tetapi akan ada penurunan daya. Selain itu, Perbandingan sensor tegangan ZMPT101B dengan alat ukur AVO meter digital saat mendeteksi tegangan memiliki error rata-rata yaitu 0,07 % untuk sensor tegangan ZMPT101B yang pertama, 0,28 % untuk sensor tegangan ZMPT101B yang kedua dan 0,15 % untuk sensor tegangan ZMPT101B yang ketiga. Sehingga dapat dikatakan bahwa sistem monitoring tegangan yang dibuat sesuai dengan ketentuan dan bisa diaplikasikan sebagai pembelajaran mahasiswa Pendidikan Teknik Elektro.